Success of palatal implants or mini-screws placed median or paramedian for the reinforcement of anchorage during orthodontic treatment: a systematic review. (28th March 2018) - Kakali, Lydia; Alharbi, Majed; Pandis, Nikolaos; Gkantidis, Nikolaos; Kloukos, Dimitrios
Summary: Objectives: To assess the failure rates of palatal implants and palatal mini-screws, independently and comparatively, used for supplementing anchorage during orthodontic treatment. Protocol and registration: The protocol was not registered prior to the study. This study was not registered in any publicly assessable database. Materials and methods: Screening for inclusion eligibility, quality assessment of studies, and data extraction was performed independently by two authors. The electronic databases MEDLINE, EMBASE, and CENTRAL, as well as unpublished literature, were searched with no restrictions on publication date or language using detailed strategies. The main outcome assessed was palatal implant or mini-screw failure. Randomized controlled trials were evaluated according to the Cochrane risk of bias tool. Prospective and retrospective studies were graded employing the adjusted predetermined criteria of Bondemark. Results: Twenty-seven studies satisfied the inclusion criteria. Four were RCTs of low risk of bias, 12 were prospective (2 low, 7 unclear, 3 high risk of bias) and 11 were retrospective studies (6 unclear, 5 high risk of bias). Only one retrospective study assessed both palatal implants and mini-screws. Seventeen studies, including the four RCTs, assessed solely palatal implants and nine studies palatal mini-screws. The median failure risk of palatal implants was 6.0 per cent (range: 0.0–26.1%) and of mini-screws 6.1 per cent (range: 0.0–33.3%). The median follow-up period was 17.9 months for palatal implants and 6 months for mini-screws. Limitations: Significant clinical and methodological heterogeneity among studies and highly variable outcomes. Conclusions: Both palatal implants and mini-screws have quite low failure rates that are also comparable, though the median follow-up period of palatal implants was quite larger. Therefore, in regular orthodontic cases, the choice between anchoring devices may rely on other factors, such as costs, patient comfort, personal preferences, familiarity with the device, and insertion procedures.